Tantangan Pendampingan Kepariwisataan Di Masyarakat Baduy - Azus, Lalu Abdul; Titi Raharjana, Destha (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
Challenges of Tourism Assistance in the Baduy Community The sustainability of rural tourism management is, among other things, determined by the ability of managers to autonomously govern their tourism. This means that the managers need to have clear guidelines to be accepted by all parties. It seems that not all tourism managers possess the necessary skills in tourism management. For instance, in Baduy, Kanekes Village, Lebak Regency, West Java, the bustling tourism that has been ongoing in Baduy has not significantly benefited its residents and environment. Some challenges faced include the suboptimal performance of local institutions with the legitimacy to regulate tourism activities, a high dependency on tour packages from external parties, and numerous external guides bringing tourists to Baduy. The environmental impacts caused by tourism and limitations in skills and human resource capacity also contribute to the challenges. This article was developed from a mentoring process conducted using a participatory action research approach. Specifically, the article aims to explain the techniques and mentoring processes conducted while highlighting the challenges encountered when assisting the Saba Budaya Baduy managers. As a result, various tourism training needs have been provided to ensure the readiness of local human resources. Post-training, mentoring continues to address challenges in implementing the training program. Mentoring challenges in the Baduy community require the mentoring team to understand the cultural values that are still maintained amidst modernity. Skills and abilities in communication with a cultural approach are essential to ensure that both physical and non-physical mentoring programs are fully accepted by the Baduy residents. The stages of tourism mentoring in indigenous communities require a continuous process to ensure that the Baduy residents have more sovereignty in tourism management.